The relationship between opening hours and accessibility of public service delivery - Neutens, T; Delafontaine, M; Schwanen, T; Van de Weghe, N (Elsevier, 2012)
In the past two decades urban time policies have been proposed and implemented in many European cities as a complement to traditional spatial planning methods. Such policies seek to provide an answer to the growing number of people facing time problems as a result of an erosion of collective time rhythms and a desynchronisation of different time structures of urban life. Particular emphasis is being placed on the reconciliation of opening hours of public service facilities with the travel and activity patterns of citizens in order to increase individual accessibility to urban services. In spite of the increasing relevance of time policies, only limited quantitative research has been conducted about the relationships between opening hours and accessibility. This paper seeks to extend this line of inquiry by exploring if and to what extent the accessibility of public facilities can be ameliorated by redesigning the timetables of service delivery. A method is proposed to optimise the temporal regime of public service delivery in terms of accessibility. The method is illustrated in a case study of accessibility of government offices within the city of Ghent (Belgium). Our findings suggest that by rescheduling the opening hours of public service facilities individual accessibility to service delivery can be improved significantly. Our study may support urban service deliverers, policymakers and urban planners in assessing timetables for a better ’accessible’ service provision.